Bernama.com editor passes away - Borneo Post, (KK) (Borneo Post (KK), 2011)
KUALA LUMPUR : Bernama.com. editor Izham Shuhaimi Ahmad died of esophageal cancer at the Selayang Hospital near here at about 4.30 pm yesterday. He was 56.